Transitions in central bank leadership - Carlos Viana de Carvalho; Tiago Flórido; Eduardo Zilberman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2017)
We assemble a novel dataset on transitions in central bank leadership in several countries, and study how monetary policy is conducted around those events. We find that policy is tighter both at the last meetings of departing governors and first meetings of incoming leaders. This finding cannot be fully explained by endogenous transitions, the effects of the zero lower bound, surges in inflation expectations, omitted variables such as fiscal policy and uncertainty nor electoral cycles. We conclude by offering two possible, perhaps complementary, explanations for these results. One based on a simple signalling story, another based on career and reputation concerns.
Keywords: 330